Association Study between Antioxidant Nutrient Intake and Low Bone Mineral Density with Oxidative Stress-Single Nucleotide Variants: GPX1 (rs1050450 and rs17650792), SOD2 (rs4880) and CAT (rs769217) in Mexican Women - Rogelio F. Jiménez-Ortega; Diana I. Aparicio-Bautista; Adriana Becerra-Cervera; Priscilla López-Montoya; Guadalupe León-Reyes; Jeny Flores-Morales; Manuel Castillejos-López; Alberto Hidalgo-Bravo; Jorge Salmerón; Berenice Rivera-Paredez; Rafael Velázquez-Cruz (MDPI AG, 2023)
Oxidative stress is essential in developing multiple bone metabolism diseases, including osteoporosis. Single-nucleotide variants (SNVs) have been associated with oxidative stress, promoting an imbalance between the production of reactive oxygen species and the ability to neutralize them, and it has been reported that antioxidant nutrient intake can influence bone mineral density (BMD). This work reports the association between oxidative stress-related SNVs (GPX1-rs1050450, rs17650792, SOD2-rs4880, and CAT-rs769217), BMD, and antioxidant nutrient intake. The study included 1269 Mexican women from the Health Workers Cohort Study. Genotyping was performed using predesigned TaqMan assays. Dietary data were collected using a 116-item semi-quantitative food frequency questionnaire. A dietary antioxidant quality score (DAQS) was used to estimate antioxidant-nutrient intake. Association analysis was estimated via linear, logistic, or quantile regression models. The results showed an association of the rs1050450-A and rs17650792-A alleles with femoral neck BMD (p = 0.038 and p = 0.017, respectively) and the SNV rs4880-A allele with total hip BMD (p = 0.026) in respondents aged 45 years or older. In addition, antioxidant-nutrient intake was associated with the rs4880-GG genotype, being significant for fiber (p = 0.007), riboflavin (p = 0.005), vitamin B6 (p = 0.034), and vitamin D (p = 0.002). The study showed an association between oxidative stress-related SNVs, BMD, and antioxidant-nutrient intake in Mexican women. Therefore, treatments for low BMD could be developed based on antioxidant supplementation.